The Competitiveness of Global Port-Cities: The Case of Hamburg, Germany - Merk, Olaf (OECD Regional Development Working Papers, 2012)
This working paper offers an evaluation of the performance of the Port of Hamburg, as well as an analysis of the port?s impact on its territory and an assessment of relevant policies and governance. It examines port performance in the last decade and identifies the principal factors that have contributed to it. In addition, the report studies the potential for synergies between the Hamburg and Bremerhaven ports. The study also considers the effect of these ports on economic and environmental questions. The value added of the port cluster of Hamburg is calculated, and its linkages with other economic sectors and regions in Germany are delineated. Specifically, the paper outlines the impact of the port?s operations, and shows how its activities spill over into other regions. The report also assesses major policies governing the port, as well as transport and economic development, the environment and spatial planning. These policies include measures instituted by the port authority and local, regional and national governments. Governance mechanisms at these different levels are described and analysed. Based on the report?s findings, proposed recommendations aim to improve port performance and increase the positive effects of the port on its territory